Implications of Equivalence for Effective Communication (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Equivalency translation is one of the most important concepts in translation, and it's usually a good place to start when explaining how language translation works. The process of accurately communicating meaning from one language to another is known as translation equivalency, and it is the core notion in the subject of translation studies. To achieve translation equivalency in this process, both encoding and decoding are essential. The importance of encoding and decoding in translation equivalency and how they support successful cross-linguistic communication will be discussed in this article